Nonspecific cervical spine pain/neck pain/in medical personnel of north-eastern Poland—A cross-sectional study - Citko, Anna; Górski, Stanisław; Marcinowicz, Ludmiła; Mateusz, Cybulski; Matylda, Sierakowska (Frontiers in Medicine, 2024)
Both mechanical and psychological overload are inherent to the work of nurses and paramedics, resulting spondylogenic pain. Aim of the study: to identify potential risk factors influencing the prevalence of non-specific cervical spine pain in professionally active nurses and paramedics. Material and methods: 324 nurses (53.2% of the total) and 285 paramedics (46.8%) were included in the study - 609 people in total. The study was carried out using an auditorium survey technique supervised by the researchers. The methods used were: Nordic Musculoskeletal Questionnaire, a spinal pain questionnaire validated according to IEA guidelines, a short version of the IPAQ and the author's survey questionnaire, concerning sociodemographic data, chronic diseases including metabolic syndrome (MetS). A univariate logistic regression model was used in the statistical analysis. The level of statistical significance was taken as p<0.05. Results: Recurrent NP was significantly more common in paramedics compared to nurses (29.5 % vs. 9.3 %; p <0.0001) . In a univariate logistic regression model, the risk of NP was significantly increased by: length of service > 15 years (p<0.024), presence of: low back pain (p<0.0001), type 2 diabetes (p=0.013), hypertension (p<0.001), depression (p<0.01). Of the modifiable factors, the risk of NP was significantly increased by high physical activity and short sleep <7 hours (p<0.001).